Validity of the Global Leadership Initiative on Malnutrition criteria in East Asian patients with gastric cancer: a comprehensive narrative review - Wang, Jian; Liu, Bingyue; Chen, Jianxin (Frontiers in Nutrition, 2024)
Background: Malnutrition is a significant public health issue for patients with gastric cancer, particularly in East Asia, the region most affected globally. In response to the absence of adequate tools for assessing nutritional status, the Global Leadership Initiative on Malnutrition (GLIM) criteria were established in 2018, aiming to standardize the diagnosis of malnutrition. However, there is no consensus on the value of GLIM criteria for evaluating the nutritional status of patients with gastric cancer in East Asia. Given these facts, our study aimed to assess the validity of the GLIM criteria in East Asian patients with gastric cancer.Methods: We conducted a rapid critical review of available literature, summarizing the existing problems in GLIM applications and possible improvement directions. After systematically summarizing the literature published in PubMed, Web of Science, and Cochrane Library, a total of 13 articles involving 7679 cases were included in this study.Results: The results indicated a lack of sufficient data on sensitivity and specificity to fully validate the GLIM criteria for diagnosing malnutrition in East Asian patients with gastric cancer.Additionally, some studies have reported moderate agreement between the GLIM and the PG-SGA. Furthermore, malnutrition defined by GLIM is a risk factor for short and long-term outcomes in East Asian patients with gastric cancer. However, the prognostic effect of moderate malnutrition on these patients remains controversial.Conclusion: Despite being in the early application stages, GLIM has shown promising potential in diagnosing and predicting the prognosis of malnutrition. However, future research should incorporate more comprehensive validity parameters, including sensitivity, specificity, and PPV/NPV, to achieve a more thorough understanding of GLIM's diagnostic efficacy. Furthermore, further optimization of GLIM is necessary to address the needs of more diverse populations and situations.